Clinical guidelines of the Russian Society of Oncomammologists for the prevention of breast cancer, differential diagnosis, treatment of precancerous and benign breast diseases - И. В. Высоцкая; В. П. Летягин; В. Г. Черенков; И. Д. Бубликов; К. П. Лактионов (Опухоли женской репродуктивной системы, 2016)
Clinical guidelines of the Russian Society of Oncomammologists for the prevention of breast cancer, differential diagnosis, treatment of precancerous and benign breast diseases